Age-dependent comparison of monoenergetic photon organ and effective dose coefficients for pediatric stylized and voxel phantoms submerged in air. (6th September 2018) - Dewji, Shaheen Azim; Bales, Kathryn; Griffin, Keith; Lee, Choonsik; Hiller, Mauritius
Abstract: Dose rate coefficients computed using the University of Florida-National Cancer Institute pediatric series of voxel phantoms were compared with values computed using the Oak Ridge National Laboratory pediatric stylized phantoms in an air submersion exposure geometry. Simulations were conducted comparing phantoms classified within five ages: newborn, 1-year-old, 5-year-old, 10-year-old, and 15-year-old for both male and female sexes. This is a continuation of previous work comparing monoenergetic photon organ dose rate coefficients, as defined by ICRP Publication 103, for the male and female adult phantoms. With both the male and female data computed for each pediatric phantom age, effective dose rate coefficients and ratios were computed for voxel and stylized phantoms. Organ dose rate coefficients for the pediatric phantoms and ratios of organ dose rates for the voxel and stylized phantoms are provided for eight monoenergetic photon energies ranging from 30 keV to 5 MeV. Analysis of the contribution of the organs to effective dose is also provided. Comparison of effective dose rates between the voxel and stylized phantoms was within 5% between 500 keV and 5 MeV and within 10% between 70 keV and 5 MeV for phantoms  >1-year-old. Stylized newborn effective dose rates were consistently ~20% higher than the voxel counterpart, over all energies.